Hydrogen gas protects against delayed encephalopathy after acute carbon monoxide poisoning in a rat model. (2nd January 2020) - Shen, Meihua; Zheng, Yijun; Zhu, Kaimin; Cai, Zhonghai; Liu, Wenwu; Sun, Xuejun; Liu, Jiankang; Zhu, Duming
ABSTRACT: Objective : The protective effects of 2%-4% hydrogen gas in delayed encephalopathy after acute carbon monoxide poisoning (DEACMP) have been previously reported. This study aimed to assess the neuroprotective effects of high concentration hydrogen (HCH) on DEACMP. Methods : A total of 36 male Sprague-Dawley rats were divided into 3 groups. In the DEACMP group, rats were exposed to CO to induce CO poisoning; in the HCH group, the animals were exposed to 67% H2 and 33% O2 at 3, 000 mL/min for 90 min immediately after CO poisoning. Neurological function was evaluated at 1 and 9 days after poisoning. Then, the contents of malondialdehyde, 3-nitrotyrosine and 8-hydroxy-2-deoxyguanosine, as well as superoxide dismutase activity in the serum, cortex and hippocampus were detected by ELISA. Additionally, the mRNA and protein expression levels of Nrf2 and downstream genes were detected by RT-PCR and Western blotting, respectively. Results : Our results showed that CO poisoning significantly impaired neurological function which was improved over time, and HCH markedly attenuated neurological impairment following CO poisoning. In addition, CO poisoning resulted in increased levels of malondialdehyde, 3-nitrotyrosine and 8-hydroxy-2-deoxyguanosine and markedly reduced superoxide dismutase activity at 1 and 9 days, which were significantly inhibited by HCH at 9 days. Finally, CO poisoning increased the mRNA and protein levels of Nrf2 and downstream genes, and HCH further induced the anti-oxidative capability. Conclusion : These findings indicate the neuroprotective effects of HCH on DEACMP, which are related to the activation of Nrf2 signaling pathway.